Chorus - Trevayne, Emma (Running Press Teens, 2014)
Pursuing an independent life with a band of her own in Los Angeles, Alpha returns to her ailing older brother's side and works with fellow revolutionaries to stop the return of Corp in the wake of increasing numbers of music-addicted victims.